The Influence of Digital Customer Experience on Customer Loyalty Mediated by Customer Satisfaction and Brand Image - Sari, Nathania Astrid Amanda; Puspaningrum, Astrid; Hussein, Ananda Sabil (Profit: Jurnal Adminsitrasi Bisnis, 2026)
This research examines the impact of Digital Customer Experience (DCE) on Customer Loyalty, with Customer Satisfaction and Brand Image Serving as mediating variables, using data from 200 MyTelkomsel mobile application users in Malang City, Indonesia. Adopting a quantitative approach and employing   Partial Least Squares – Structural Equation Modeling (PLS-SEM), the research examines both direct and indirect relationships among the variables. The results show that DCE has a significant positive impact on customer satisfaction, brand image, and loyalty. Moreover, customer satisfaction mediates the relationship between DCE and loyalty, whereas brand image does not act as a significant mediator. These findings suggest that functional and experiential factors such as usability, security, and responsiveness play a greater role in driving loyalty than perception-based elements like brand image. In mobile app contexts, loyalty is more likely when digital interactions are consistently satisfying. The results support the Service Dominant Logic theory, highlighting the importance of value co creation between users and service providers through digital engagement. Practically, telecommunications companies should focus on enhancing user-centric features, personalisation, and interface optimisation to foster long-term customer retention in an increasingly competitive digital environment.